Bringing italians SME’s to Brazil: the case of GM Venture - Fumagalli, Chiara (2016)
The Italian business presence in Brazil has been characterizing, since years, the economic landscape of Brazil. More than 1300 Italian companies, from the biggest to the smallest one, are acting in Brazil, exploiting the overall potential of this country and contributing with the excellence they can bring. Noting the consistency of the Italian presence and wondering how those companies have entered such a complex country and, a recurring name has been GM Venture, which became the protagonist of this dissertation. The thesis in fact aims at studying how GM Venture Company has been able to create value for Italian SMEs, contributing to their success in Brazil during the last ten years. Therefore this analysis focuses firstly on the literature dealing with the key success factors for the internationalization of small-medium enterprises. The second part of the literature goes deep in the specific case of the Brazilian context, trying to understand the major problems that this particular environment poses to small-medium companies internationalizing here and some specific factors Italian companies should pay attention to. Given this introduction, the analysis centers on the core topic of this dissertation. In fact the investigation regarding the GM Venture case looks specifically at how this company has been able create value despite those problems and create a business model able to successfully support SMEs entering Brazil. The inquiry on the case and the conclusion reports how GM Venture, through its operations, has been able to respond to the Brazilian rtise, and positively contribute to the growth and value of the Italian economic reality in this country. Moreover looking at the literature findings, this specific case introduces some novelty in the emerged factors, such as a new way of conceiving the Network, as well as new factors or undervalued ones for success such as promptness in the response and trustworthiness, which are essential in the Brazilian economic environment.